Laboulbeniales (Fungi, Ascomycota) of Cholevine beetles (Coleoptera, Leiodidae) in Belgium and The Netherlands - De Kesel, A.; Haelewaters, Danny (Antwerpse Mycologische Kring, 2019)
This paper presents new records of Laboulbeniales from cholevine hosts (Leiodidae, Cholevinae) in Belgium and the Netherlands. Corethromyces henrotii was found on Choleva cisteloides, C. fagniezi, C. jeanneli and C. oblonga; it is a first record for the Netherlands. Diphymyces kaaistoepi is a newly described species on Choleva cisteloides and C. fagniezi. Two host insects carried thalli of both C. henrotii and D. kaaistoepi, apparently without specific growth positions. Descriptions and illustrations are given for both taxa.
Keywords: Choleva; Corethomyces; Diphymyces; ecology; taxonomy